PROBLEMS IN THE PUBLIC PROCUREMENT PROCESS IN LOCAL GOVERNMENTS IN INDONESIA (Case Study : Blitar Regency and Batu Municipality) - Damayekti Intan Permatasari (JURNAL TECNOSCIENZA, 2017)
Indonesian local governments must put to bid all construction works that will cost more than 16,950 according to Presidential Regulation No. 35 of 2011. The local governments always use the Knockout System in the auction process which has a different auction flow with the Presidential Decree No.80 of 2003. Research data were obtained through questionnaires and surveys in the Blitar Regency and the Batu Municipality, and methods were used to describe the analysis and Importance-Performance Analysis (IPA). The auction process should be conducted through some evaluations, such as the administrative evaluation, technical and the final evaluation of technique and costs. These are different from the bidding process of Direct Appointment with the Public Tender in the located Arithmetic. The Public Tender must have a Pre-Occupational Safety and Health Plan Contract (Pre-RK3K) and Quality Management to pass the Administration Evaluation, but the Direct Appoinment was not the main requirement of the bidding process.Keywords: Electronic procurement system, Knockout System, Importance-Performance Analysis